Coplanar waveguide‐FED planar spiral antenna with integrated impedance transformer. Issue 6 (27th March 2013) - Vahidpoor, Zeynab; Forooraghi, Keyvan; Fotowat‐Ahmady, Ali; Atlasbaf, Zahra
Abstract A new planar spiral antenna with integrated impedance transformer is presented which needs no external balun and can be fed by a coplanar waveguide.The proposed structure has a return loss of <−10 dB over a broad bandwidth of 0.5–5 GHz that is suitable for cognitive radio applications. The effects of different spiral and transformer parameters are investigated through various simulations. A case of the proposed antenna is fabricated, and measurement results are presented including return loss, gain, and radiation patterns. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1338–1341, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27535